Preparing Today’s Teachers for Tomorrow’s Children - Socorro Herrera; Robert Fanning (Educational Considerations, 1999)
Today’s social reality requires that educators throughout the United States face the challenges of teaching and preparing culturally and linguistically diverse students in the classroom.